Improving the gel properties of duck egg white by synergetic phosphorylation/ultrasound: Gel properties, crystalline structures, and protein structure - Hui Xue; Huilan Liu; Na Wu; Guowen Zhang; Yonggang Tu; Yan Zhao (Ultrasonics Sonochemistry, 2022)
To improve the gel properties of duck egg white gel and increase the industrial value of duck egg white, the mechanisms of ultrasound and synergetic phosphorylation/ultrasound treatments were examined in this study. It was found that as the ultrasound power increased, the surface hydrophobicity, hardness, and cohesiveness of the gel system increased, and the ζ-potential and water mobility decreased. Of the two treatments, phosphorylation/ultrasound had the strongest impact on the conformation and crystallinity of the gel system and promoted the formation of high molecular polymers. Both gel systems displayed enhanced compactness, stability, and gel strength because of the enhanced protein–protein interactions via hydrogen bonds and protein aggregation, and increased the content of intramolecular β-sheets following ultrasound treatment, and synergetic phosphorylation/ultrasound further improved the stability, water binding and gel properties. This experiment showed that ultrasound and, particularly, phosphorylation/ultrasound are effective methods to improve the gel properties of duck egg white. This study enhanced our understanding of the interactions of sodium pyrophosphate and egg white under ultrasound treatment, and promote the potential application of sodium pyrophosphate and ultrasound treatment of novel food products.